2021
DOI: 10.1108/lht-03-2021-0103
|View full text |Cite
|
Sign up to set email alerts
|

Library café or elsewhere: usage of study space by different majors under contemporary technological environment

Abstract: PurposeAs current university students may access information for their study anytime, anywhere with ubiquitous mobile technologies, this research re-examines the roles of study space in students' learning and campus life.Design/methodology/approachA survey was conducted to collect students' opinions and habits regarding the usage of different study spaces. Results in three different academic majors (science and engineering, arts and business) of a comprehensive international university were compared.FindingsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…The present findings provide essential foundations for suggesting various strategies for redesign library places to meet diversified student needs under the fast-changing globalized technological knowledge economy. The present findings also provide further insight on how the COVID-19 pandemic has re-defined academic libraries on space planning (Zhou et al , 2021), on top of the existing findings on their roles and services (Fasae et al , 2021; Meng et al , 2021), mobile apps designs (Fung et al , 2016) and on developing a higher level of social capital (Fong et al , 2020).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The present findings provide essential foundations for suggesting various strategies for redesign library places to meet diversified student needs under the fast-changing globalized technological knowledge economy. The present findings also provide further insight on how the COVID-19 pandemic has re-defined academic libraries on space planning (Zhou et al , 2021), on top of the existing findings on their roles and services (Fasae et al , 2021; Meng et al , 2021), mobile apps designs (Fung et al , 2016) and on developing a higher level of social capital (Fong et al , 2020).…”
Section: Discussionsupporting
confidence: 56%
“…on space planning (Zhou et al, 2021), on top of the existing findings on their roles and services (Fasae et al, 2021;Meng et al, 2021), mobile apps designs (Fung et al, 2016) and on developing a higher level of social capital (Fong et al, 2020).…”
Section: Appendix Survey Itemsmentioning
confidence: 99%
“…Noh (2022) investigated the library as a complex cultural space and showed that library users participated and enjoyed its services and programs. On the other hand, Zhou et al (2022) investigated the library caf e as a study space. They showed that the library caf e is essential for students' learning and life.…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…They noted that library users adjusted themselves to use these facilities with social distancing in their minds. Concerning this, readers may compare the results of their findings with those done before COVID-19 under the same context (Zhou et al , 2021; Chan et al , 2020), as well as the study on cultural library spaces by Noh (2021). Yu et al (2022) also summarized some pragmatic operation management measures of libraries in Hong Kong under COVID-19.…”
Section: Re-engineering In Learning and Library Services During The P...mentioning
confidence: 99%